Faith and work : Christian research, perspectives, and applications - Ewest, Timothy (Advances in workplace spirituality., 2022)
The continued presence and growth of religion within the global community, resists the notion that religion is to be usurped by the secular or disenfranchised through secularism. Instead, contemporary scholarship emerging from an array of academic disciplines, continues to support religions' presence and impact on individuals, organizations and society. For example, the last two centuries offer an array of scholarship which understands religion to be formative for personal identity, instrumental in coping with suffering, an iterative force in social construction, dynamic in its historical perception and having an ever present role in culture, politics and society.However, the role of religion in the workplace is still resisted by some scholars of note in the Academy of Management. Yet, scholarship regarding the impacts of religion on societal, organizational and individual life continues to grow, carrying on the long standing research tradition of Weber. Scholarship has explored connections and manifestations of the world's religions within the workplace. Within Christianity, examples of research considerations within Catholic traditions, beliefs and practices which undergird workplace practices have been given ample consideration and alternatively examples of Protestant beliefs and practices within the workplace continues to grow. This second volume continues the work of the first volume of Faith and Work, Christian Perspectives, published in 2018. As with the first volume, this second volume considers Christian perspectives, research and insights into the faith and work movement, delimitating research into one of three areas: Individual, organizational and societal dimensions.Again, this volume, like the first contains scholarship from nationally and internationally recognized scholars whose research understands and demonstrates the importance of the connections between the Christian faith and the workplace. The scholarship presented in this volume is considered cross disciplinary, as was the first volume which was presented at the Cultural Study Association (CSA) Conference held at Carnegie Mellon University, the Society for the Scientific Study of Religion (SSSR) conference held in St. Louis, Missouri and also at the 2019 Academy of Management, Boston, MA. The first book has also enjoyed use in masters and doctoral programs as a supplemental reader.